2017
DOI: 10.1108/ecam-02-2016-0038
|View full text |Cite
|
Sign up to set email alerts
|

An appraisal of paradigm shifts required of competence of the Nigerian quantity surveyors

Abstract: Purpose The purpose of this paper is to investigate the competence of Nigerian quantity surveyors with a view to identify and assess required areas of interest. Design/methodology/approach A structured questionnaire was administered among relevant groups of respondent (quantity surveyors, architects, engineers, builders and clients) in Nigeria. The respondents were asked to give rating, on a five-point Likert scale, on the required competencies (variables) expected of Nigerian quantity surveyors. A mean item… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
(19 reference statements)
0
8
0
Order By: Relevance
“…Musa et al (2010) concluded that harnessing appropriate ICT tools would improve the quality of quantity surveying services in the country. In addition, several other studies have buttressed this assertion (Ibironke et al, 2011;Olanrewaju, 2016;Dada and Musa, 2016;Dada, 2017). There is a clear-cut evidence that ICT has numerous benefits but the implementation in practice is one of a different story in the Nigerian construction sector (Oladapo, 2006;Waziri et al, 2015).…”
Section: State Of Bim In the Nigerian Construction Industrymentioning
confidence: 98%
See 2 more Smart Citations
“…Musa et al (2010) concluded that harnessing appropriate ICT tools would improve the quality of quantity surveying services in the country. In addition, several other studies have buttressed this assertion (Ibironke et al, 2011;Olanrewaju, 2016;Dada and Musa, 2016;Dada, 2017). There is a clear-cut evidence that ICT has numerous benefits but the implementation in practice is one of a different story in the Nigerian construction sector (Oladapo, 2006;Waziri et al, 2015).…”
Section: State Of Bim In the Nigerian Construction Industrymentioning
confidence: 98%
“…In general, a review of the existing literature of ICT adoption in Nigeria revealed shortcomings in BIM implementation and education in comparison with what is obtained globally. In the light of the above, Dada (2017) opined that there is need to understand the identified gap in construction education provided by relevant stakeholders, especially the academic institutions offering QS programmes in Nigeria.…”
Section: >>>>>>>>> Insert Table I>>>>>>>>>>>mentioning
confidence: 99%
See 1 more Smart Citation
“…to evaluate competency attributes, where H0 is rejected when p < 0.05. In order to determine the level of significance, mean scores were calculated by averaging all scores of the respondents for each competency -a tool which has been widely employed in construction management (Amoatey and Danquah, 2018;Oke and Otasowie, 2020) and competence-related (Dada, 2017;Kwofie et al, 2018) studies. The mean values range from 1 to 5 (extrapolated from the Likert-scale points).…”
Section: Methodsmentioning
confidence: 99%
“…Amoatey and Danquah, 2018; Oke and Otasowie, 2020) and competence-related studies (e.g. Dada, 2017; Kwofie et al , 2018). The mean values range from 1 to 5 (extrapolated from the Likert scale points).…”
Section: Methodsmentioning
confidence: 99%